Emotional Intelligence and Musical Activity: An Ex-Post Facto Study of Musical Practice in Indonesia - Wardani, Indra Kusuma (Graduate School of Institut Seni Indonesia Yogyakarta, 2025)
The importance of emotional intelligence in maximizing individual potential has sparked various studies related to this topic. In addition to research focusing on the mechanisms of emotional intelligence, several studies aim to explore ways to develop these skills more efficiently. Music has not escaped the attention of researchers due to numerous claims about its potential to enhance intelligence and optimize individual potential. One such area of focus is ensemble activities in both instrumental and vocal group contexts. The argument and theoretical framework supporting the potential of musical activities to improve emotional intelligence are based on the characteristics of routines in ensembles that overlap with general indicators of emotional intelligence. This research examines the influence of musical ensemble activities on emotional intelligence through an ex-post facto study involving 104 subjects divided into three groups using the adaptation of Goleman's emotional intelligence questionnaire. The subjects are orchestra musicians, choir singers, and those not engaged in musical activities. The selection criteria for musicians/choir singers involved in this study are as follows: They must have at least 5 years of experience in music ensemble. Based on a one-way ANOVA test, there was a significant difference in emotional intelligence scores according to the type of musical activity participated by the respondents (F(2,101) = 5.254, p=.0007). Post-hoc analysis using the Bonferroni correction revealed a significant difference between the group that did not participate in musical activities and the choir group (p=.006), with higher emotional intelligence scores observed in the choir group. No significant differences were found between the orchestra/ensemble group and the other groups (p>.05) Kecerdasan Emosional dan Aktivitas Musikal: Studi Ex-Post Facto Praktik Musik di Indonesia Abstrak Pentingnya kecerdasan emosional dalam memaksimalkan potensi individu telah memicu berbagai penelitian terkait topik ini. Selain penelitian yang berfokus pada mekanisme kerja kecerdasan emosional, beberapa studi juga bertujuan untuk mengeksplorasi cara-cara mengembangkan keterampilan ini secara lebih efektif. Musik tidak luput dari perhatian para peneliti karena banyak klaim mengenai potensinya dalam meningkatkan kecerdasan dan mengoptimalkan potensi individu. Salah satu fokus kajiannya adalah aktivitas ansambel, baik dalam konteks kelompok vokal maupun instrumental. Argumen dan kerangka teoritis yang mendasari potensi aktivitas musikal dalam meningkatkan kecerdasan emosional didasarkan pada karakteristik rutinitas dalam ansambel yang tumpang tindih dengan indikator umum kecerdasan emosional. Penelitian ini mengkaji pengaruh aktivitas ansambel musik terhadap kecerdasan emosional melalui studi ex-post facto yang melibatkan 104 subjek, yang dibagi ke dalam tiga kelompok berdasarkan adaptasi kuesioner kecerdasan emosional dari Goleman. Subjek terdiri dari musisi orkestra, penyanyi paduan suara, dan individu yang tidak terlibat dalam aktivitas musikal. Kriteria pemilihan musisi dan penyanyi paduan suara dalam studi ini adalah memiliki pengalaman minimal 5 tahun dalam aktivitas ansambel musik. Berdasarkan hasil uji ANOVA satu arah, ditemukan perbedaan yang signifikan dalam skor kecerdasan emosional berdasarkan jenis aktivitas musik yang diikuti oleh responden (F(2,101) = 5.254, p = 0.007). Analisis post hoc menggunakan koreksi Bonferroni menunjukkan adanya perbedaan yang signifikan antara kelompok yang tidak mengikuti aktivitas musik dan kelompok paduan suara (p = 0.006), dengan skor kecerdasan emosional yang lebih tinggi pada kelompok paduan suara. Tidak ditemukan perbedaan yang signifikan antara kelompok orkestra/ansambel musik dengan kelompok lainnya (p > 0.05).